The Influence of Corporate Social Responsibility (CSR) and Liquidity on Firm Value: Role Moderation Size Company on Property Real Estate and Construction Company - Nurkomala, Nita; Fauzia, Putri; Yulianto, Agung (Dinasti Publisher, 2025)
Increasing the worth of the company is one of its main goals in order to attract investors. One of the most crucial components is firm value since it can serve as a benchmark for business performance, which investors can assess from the perspective of corporate social responsibility. The study's goal is to look into how corporate social responsibility and things that affect cash flow affect the value of a company. The study also seeks to know how company size affects income and liquidity-firm value relationships. The analysis includes IDX-listed companies from 2020 to 2023. The sampling method was taken using a purposive sampling table with predetermined criteria, the data that fell into the criteria were 33 data samples. MLR and MRA analyzes were done in SPSS 25 to evaluate this notion. This study found that firm size moderates the CSR-firm value link. On the other hand, CSR boosts firm value. Even though liquidity doesn't change firm value, company size doesn't affect the link between liquidity and value.